Imbach, Rudi: Aristoteles in der Hölle. Peregrina Curiositas - ter Reegen, Jan Gerard Joseph (Kairós, 2021)
Imbach, Rudi: Aristoteles in der Hölle. Peregrina Curiositas. Freibur/Göttinngen, 1994, p. 299-318.